Tofacitinib Citrate for Ulcerative Keratitis in a Patient with Rheumatoid Arthritis. (16th June 2014) - Meadow, Philip B.; Nguyen, Jacqueline; Kesavarapu, Keerthana
Abstract : Purpose. To report a case of a patient with rheumatoid arthritis (RA) treated with tofacitinib citrate. Methods. Observational case report. Results. A 59-year-old patient, with a history of rheumatoid arthritis, on methotrexate 10 mg PO qwk and IV abatacept 750 mg/month, presented with photosensitivity, foreign body sensation, pain, redness, and blurry vision of her right eye (RE). Visual acuity of the RE was 20/200 and 20/20 of the left eye (LE). The slit lamp examination of the RE revealed dryness, 2+ injection of the conjunctiva, and pericentral ulceration of the cornea with 20–30% stromal thinning, pannus, and diffuse punctate epithelial erosions. The anterior chamber appeared normal. Laboratory values revealed elevated levels of rheumatoid factor, anticyclic citrullinated peptide antibodies, and C-reactive protein. The patient was switched to tofacitinib citrate 5 mg PO b.i.d, underwent corneal gluing, and was given prednisone acetate 1% gt TID, polytrim gt TID, neomycin-polymyxin-dexameth gt QD, FreshKote lubricant 1.8% gt QID, moxifloxacin 0.5% gt QID, and preservative free artificial tears Q1H. Within one week, laboratory values normalized, symptoms diminished, and the cornea reepithelialized. Conclusion. RA can present with ulcerative keratitis. Tofacitinib citrate, steroids, and corneal gluing were found to halt the progression of keratolysis and promote reepithelialization.